Suatu Tinjauan tentang Tenaga Kerja Buruh di Indonesia - Idi Setyo Utomo (The Winners, 2005)
Article discusses problems faced by the labor in Indonesia. To make a good relationship between companys’ owner and labor, there will be an active and positive role of bipartit department in the company. In order to make an indutrial relationship is in harmony in the future, it is suggested that every problem in the company should be solved by the bipartit department with “win-win solution”.